Transformation of the state defense paradigm in building the nation's information and cognitive resilience in the era of global disinformation - Anton Nugroho; H.A Danang Rimbawa; Danny Setyowati (International Enterprise Integration Association, 2026)
The escalation of global disinformation has redefined the meaning of national defense, shifting it from a conventional military paradigm to a contested cognitive domain that challenges the integrity of truth and the resilience of public reason. This study addresses the problem of Indonesia’s fragmented and reactive defense policy in responding to the intensifying threats of information warfare that undermine democratic stability and societal cohesion. The research aims to formulate a transformative framework for national defense that prioritizes information resilience and cognitive preparedness as strategic pillars of sovereignty. Employing a systematic literature review (SLR) guided by the PRISMA 2020 protocol, the study analyzed 610 relevant academic and policy documents published between 2016 and 2025. The findings reveal that Indonesia’s national information defense remains dominated by defensive and bureaucratic approaches, weakened by poor inter-agency coordination, limited digital human resource competence, and the absence of a permanent coordinating body. Compared to Finland and Germany, Indonesia still treats digital literacy as an auxiliary policy rather than a strategic defense tool. The study concludes that safeguarding the state in the digital era requires reconstructing national defense policies toward an integrated, anticipatory, and human-centered system that transforms citizens into cognitive defenders of truth within a resilient and democratic information ecosystem.